O papel do trânsito de cálcio e de compostos da matriz extracelular no modelo de insuficiência aórtica aguda experimental em ratos - Bussoni, Márjory Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The mechanisms that are involved in cardiac remodeling by volume overload and the moment the eccentric hypertrophy has impaired cardiac function are largely unknown. Objectives: a) to compare morphological, cell (hypertrophy) and interstitial (fibrosis) changes at different times of the evolution of aortic regurgitation (AR); b) to analyze which of the following mechanisms are involved in cardiac remodeling induced by aortic failure and at what moment this change takes place: change in the metalloprotease 2 (MMP 2) and tissue inhibitor of metalloproteinase 1 (TIMP1); changes of messenger RNAs to code proteins involved in calcium homeostasis (phospholamban, Ryr and SERCA2a), changes in expression of phospholamban and SERCA2a in the calcium transit. Methods: Experimental study with 64 male Wistar rats, 32 animals submitted to acute aortic regurgitation (AR group) and 32 animals sham procedure (Sham group). All animals were followed with 1, 4, 8 and 12 weeks by serial echocardiography and after euthanasia, were analyzed morphometry of cardiac tissue, the activity of MMP2 and TIMP-1, gene expression by RT-PCR of calcium homeostasis protein, SERCA2a and phospholamban expression by Western Blotting. Statistical analysis was performed by two-way ANOVA; the Holm Sidak post test; t test group to group; Anova one way, complemented by Tukey; Bonferroni correction; Spearman correlation test and Pearson's correlation test. In all cases, the significance level was set at p <0.05. Results: In the first week it was observed that weight of the LV and diastolic blood pressure were higher in the AR group. In the fourth week, MMP 2, TIMP-1, and collagen fraction were higher in the AR group. The myocyte area and left ventricle diastolic diameter (LVDD) were higher in the AR group compared to the sham group, from the eighth week. At weeks 8 and 12, the wall thickness (WT) was higher in the AR group than the...

Os mecanismos envolvidos na remodelação cardíaca por sobrecarga de volume e o momento que a hipertrofia excêntrica apresenta prejuízo da função cardíaca são pouco conhecidos. Objetivos: a) Comparar alterações morfofuncionais, celulares (hipertrofia) e intersticiais (fibrose) em diferentes momentos da evolução da insuficiência aórtica; b) Verificar quais dos seguintes mecanismos estão envolvidos na remodelação cardíaca induzida pela IAo e em qual momento esta alteração acontece: alteração na metaloprotease 2 (MMP2) e do inibidor tecidual de metaloprotease 1 (TIMP1), alterações dos RNAs mensageiros específicos para a codificação das proteínas envolvidas na homeostase do cálcio (Fosfolambam, Ryr e Serca2a), alterações da expressão de proteínas fosfolambam e Serca2a do trânsito de cálcio. Casuística e Métodos: Estudo experimental com 64 ratos Wistar machos, 32 animais submetidos à insuficiência aórtica aguda (grupo IAo) e 32 animais a procedimento simulado (grupo Controle). Todos os animais foram seguidos com 1, 4, 8 e 12 semanas através de ecocardiogramas seriados e, após eutanásia, foram analisada morfometria do tecido cardíaco, atividade da MMP2 e TIMP-1, expressão gênica por Reação em Cadeia da Polimerase em Tempo Real das proteínas do trânsito de cálcio, expressão das proteínas Serca2a e fosfolambam pela técnica Western Blot. A análise estatística foi efetuada pela ANOVA de dois fatores; o pós teste de Holm Sidak; teste t grupo a grupo; Anova de 1 via, complementada por Tukey; correção por Bonferroni; teste de correlação de Spearman e teste de correlação de Pearson. Em todos os casos, o nível de significância adotado foi p<0,05. Resultados: Observou-se, na primeira semana, que o peso do VE e a pressão diastólica foi maior no grupo IAo. Na quarta semana, MMP2, TIMP-1, iMVE e fração de colágeno foram maiores no grupo IAo. A área do miócito e DDVE foram maiores...
Keywords: Insuficiência aórtica; Colágeno; Cálcio; Homeostase; Metaloproteases; Aortic valve insufficiency